Die effektiwiteit van verskillende leergeleenthede vir psigiatriese verpleegkunde studente vir die aanleer van interpersoonlike vaardighede - L.R. Uys (AOSIS, 1985)
The effectiveness of learning opportunities involving either laboratory or real clinical situations in interpersonal skills as reflected by an empathy scale was evaluated. It was found that the laboratory experience effected a significantly larger gain in empathy.